Meningkatkan Keterampilan Proses Peserta Didik Kelas VIII SMP Negeri 12 Kota Ternate Materi Konsep Hukum Newton Melalui Peneraan Model Pembelajaran Berbasis Masalah - Endang Fitria (Peneliti.net, 2022)
The research conducted at SMP Negeri 12 Kota Ternate was a classroom action research using a problem-based learning model which was carried out in two cycles. The subjects of this study were 23 students of class IIC SMP N 3 KotaTernate. Students' process skills are measured based on the increase in the percentage of students' process skills classically. The instrument used is an observation sheet to measure science process skills. Final data analysis on improving science process skills in the observation class on medium criteria with a gain factor of 0.35 and in cycle 1 class on low criteria with a gain factor of 0.25. The results of this study indicate that the gain factor value for cycle 1 class is higher than the control class gain factor value in terms of increasing mastery of concepts and science process skills. Thus the application of the problem-based learning model is more effective for improving students' science process skills compared to the DI learning model on motion material.